Efektivitas Terapi Latihan terhadap Kemampuan Fungsional Post Rekonstruksi ACL Grade 2 - Djawas, Faizah Abdullah; Prasasti, Prasasti (Jurnal Fisioterapi Terapan Indonesia, 2022)
Introduction: Anterior Cruciate Ligament rupture is a condition with a tear in the ACL ligament, caused by direct or indirect contact in the knee. Various problems in patients with post-ACL reconstructions include a limited range of motions (ROM), decreased muscle strength, and decreased functional ability. Exercise therapy in CKCE, OKCE, and core stability is believed to improve functional abilities by decreasing pain and improving ROM and muscle strength. The purpose of this study is to determine the effectiveness of exercise therapy on functional ability in post-reconstructionACL grade 2. Method: Single case study, physiotherapy intervention in a 19-year-old male. Exercise therapy in CKCE, OKCE, and core stability is given three times per week, with five evaluations. Assessment of pain intensity using VAS, ROM using a goniometer, muscle strength with MMT, and functional ability using IKDC parameters. Result: This study finds a decrease in pain, an increase in ROM and MMT, and an increase in functional abilities. Conclusion: Exercise therapy interventions with CKCE, OKCE, and core stability exercise improve functional ability in post-reconstructionACL grade 2 cases measured by IKDC parameters.